Organisational practices and individual innovation behaviour: a non-linear approach to modelling the emergence of corporate entrepreneurship - Hind, Colene (Graduate School of Business (GSB), 2019)
Background: Successful corporate entrepreneurship is credited with various positive organisational outcomes and achievements. At the wellspring of corporate entrepreneurship is the individual member of the organisation tasked with innovative behaviour. Corporate entrepreneurship emerges within the interface between innovative individuals and the organisational system they function in. Classical theorising that follows reductionist approaches in the pursuit of pure causality has failed to explain the emergence of corporate entrepreneurship within the dynamic and non-linear processes that constitute the complexity embedded in organisations. Research statement: Corporate entrepreneurship as an emergent process within an organisation comprises various elements that when studied through classical theories and methods fail to explain the process as a whole. An alternative theory and method is needed if corporate entrepreneurship is to be understood as a complex, dynamic and non-linear phenomenon. Method of analysis: A two-phase sequential explanatory mixed method of analysis is employed. Quantitative data, that was gathered using existing measuring instruments, includes variables related to human capital and organisational practices and individual innovative behaviour. The data is presented to the Self-Organising Maps software, which utilises the principles of Artificial neural networks to cluster it. Phase 2 comprises a qualitative exploration with subject matter experts, of outlying cluster patterns produced by the quantitative results. Findings and conclusions: Theoretically, the study describes the relevant concepts of corporate entrepreneurship and organisational practices and complex adaptive systems theory as they pertain to the study. Empirically, the study maps the emergence of innovative behaviour in a manner that explores an alternative to mainstream purist causality. The study produces a conceptual framework that can be contextually adapted and applied in practice to gain understanding into the emergence of corporate entrepreneurship. The study concludes that our understanding of the emergence of corporate entrepreneurship can be enhanced through the use of methods that allow for the non-linear and dynamic nature of the phenomenon, rather than methods that attempt to reduce it.